Administration Reagent of Aceh Family Law Qanun: Siri Marriage Motives Towards the Legality of Polygyny - Amirulkamar, Said; Iskandar, Iskandar; Zuhrah, Fatimah; Anzaikhan, M. (Shariah Faculty UIN Maulana Malik Ibrahim Malang, 2023)
The proposal of qanun on polygyny by the Acehnese elite (executive and legislative) was aimed at the wider community because of the rampant phenomenon of siri marriage. Siri marriage is not prohibited in Aceh, and administrative requirements are even relaxed for ordinary people. This gap raises the question of whether the Acehnese elite proposed qanun polygyny for the benefit of the community or for subjective interests. This article is classified as field research with a qualitative approach. The methodology used is a descriptive-analytical study. The results of the study found that the administration reactor or key factor of the family law qanun in Aceh lies in the condition where the administration of polygyny requirements is tightened beyond the provisions of The Compilation of Islamic Law (KHI) and Siri Marriage requirements are loosened under the KHI provisions. The motive was an attempt by Acehnese elites to have their siri wives recognized (legality) in Aceh's polygyny qanun. This finding can be an input for family law studies to create regulations that are more objective and independent, especially in regions that have special autonomous rights.